Field notes contributed by Barbara L. Wilson, spring 1988 - Wilson, Barbara L.et al (1988)
List of birds and locations contributed by Barbara L. Wilson with observer Babs Padelford. The field notes include an additional page of birds observed by others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed/flatbed